A novel study for determining early life degradation of multi-crystalline-silicon photovoltaic modules observed in western Himalayan Indian climatic conditions. (September 2016) - Sharma, Vikrant; Chandel, S.S.
Highlights: Early degradation is observed in m-C-Si modules of a photovoltaic system installed in a Himalayan location. Snail trails, single cell browning and junction box failure are observed in all the PV modules. Degradation analysis is carried out by visual inspection, thermal imaging and I–V characteristic measurements. Peak power degradation in IEC certified modules was found to be more than expected level in some modules. Outcome of the study will be useful in understanding climate specific field degradation mechanism. Abstract: The results of a first time study are reported on the degradation of a roof mounted multi-crystalline-silicon photovoltaic system after 2.5 years of outdoor exposure in a western Himalayan location in India. The main objective of the study is to identify frequently occurring defects in modules to study the change in electrical performance parameters and correlate these with identified defects under Indian climatic conditions. A comprehensive test campaign is conducted by visual inspection, thermal imaging and current–voltage characteristic measurements. Early degradation and recently reported defect: snail trails are observed in all modules along with non-uniform single cell browning and junction box failure. Thermal imaging analysis is carried out which shows that three modules developed serious defects like hotspots, disconnected cells and string interconnect ribbons and a significant result that all solar cells located directly on top of junction boxes were 3–8 °C hotter than other cells indicating higher thermal degradation rate of these cells than others. Peak power degradation of modules is quantified by measuring performance parameters under standard test conditions as a function of field exposure time, using class-A sun-simulator. Three modules showed 50% degradation while remaining seven modules showed 0.6–2.5% degradation in peak power after 2.5 years. PV modules certified as per International Electro-technical Commission (IEC) standards have shown considerable degradation indicating the need to enforce quality control and review qualification standards for Indian climatic conditions if modules have to perform reliably for more than 20 years under field conditions. The outcome of the study will be of importance to enhance the knowledge of climate specific field PV degradation mechanism and to provide inputs to Indian/IEC standards, the improvements of which are being considered currently.